Disaster Recovery Dengan Proxmox Ha Cluster Dan Freenas Untuk Menambah Availability Server - Albar, Arditya Devrian, Helman Muhammad, S.T., M.T (2016)
The server is a computer system that served as a service provider for the client. With server functions which provide services to the client, the server is required to have a high level of availability. But surely there will be a problem that can cause the server able to fulfill his duties as a service provider, whether it's a natural disaster or a disaster caused by human error. For that we need a disaster recovery to overcome it. This research aims to design a disaster recovery by creating a cluster computer system built from two virtual servers with the operating system Proxmox VE 3.4. The system is built to minimize server downtime and increase the level of availability server. In addition to using a computer cluster to support the design of disaster recovery, also needed a method of shared storage that is used as a data center built on a single virtual server with FreeNAS operating system. Based on the research results obtained were almost close to zero downtime. In tests conducted several times gained an average delay time of 0.39 minutes with a total availability rate reached 99.32%, so the virtual cluster system this can be a solution to improve the system with a high level of availability.